Atypical work: a threat to labour productivity growth? Some evidence from Italy. Issue 5 (2nd September 2016) - Bardazzi, Rossella; Duranti, Silvia
Abstract: Various theories suggest the existence of a negative relationship between the use of atypical employment contracts and productivity growth, arguing that firms' utilisation of atypical contracts may reduce the incentive to innovate and internal training, inducing firms to follow a 'low-road' to competitiveness, based upon cost-cutting strategies. This paper aims to provide new evidence on the occurrence of these effects in the Italian economy, where changes in labour legislation from the mid-Nineties onwards, associated with an 'institutional' wage moderation period, have brought about a significant process of job creation, but also an appreciable slowdown in labour productivity. This issue is investigated using a microeconomic approach, taking a rich source of microdata for firms and estimating a dynamic model for labour productivity on a pseudo-panel of firms for the period 2003-2008. The results support the hypothesis of a negative impact of external labour flexibility on labour productivity growth at firm level, such effect proving stronger for small and medium than for large enterprises and of varying magnitude for the different atypical contracts.